Effect of Zinc Application on the Nutrient Content of Wheat (Triticum aestivum L.) Irrigated with Different Saline Waters - Dogra, Prerna; Yadav, B L; Qureshi, F M (Annals of Arid Zone, 2016)
The efficiency of zinc application on the performance of wheat (Triticum aestivum L.) irrigated with different saline waters was studied in pot experiment on sandy clay loam soil. The experiment was laid out in CRD with four (W0, W1, W2, W3) qualities of irrigation water and four levels of zinc (0, 5, 10 and 15 mg kg-1 soil). High ECiw significantly reduced the grain and straw yield, phosphorus, potassium and zinc contents in grain and straw, while sodium content increased. Zn application to soil had favorable effect on grain and straw yield of wheat. The Zn increased the contents of N, K, Zn significantly in both grain and straw whereas, phosphorus content was decreased significantly. The comparative reduction in grain and straw yield of wheat as well as contents of P and Zn of grain and straw was less at higher doses of zinc sulphate when the level of ECiw increased in irrigation water. Hazardous effects of saline water on wheat can be mitigated to some extent by applying zinc sulphate at the rate of 15 mg Zn kg-1 soil. Key words: Saline water, zinc, wheat, yield.